PENGEMBANGAN BAHAN AJAR STATISTIKA DENGAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING UNTUK MEMFASILITASI KEMAMPUAN KONEKSI MATEMATIS SISWA - Putri, Amanda Handya; Armis, Armis; Syofni, Syofni (Faculty of Educational sciences, UIN Syarif Hidayatullah Jakarta, 2023)
AbstractThis research aims to develop instructional materials for teaching statistics using a contextual teaching and learning strategy. The goal is to enhance the mathematical connection abilities of eighth-grade junior high school students. The materials are designed to meet the criteria of validity and practicality. The present study involves the development of a 4-D model, encompassing the stages of Define, Design, Develop, and Disseminate. The validation process was carried out by involving three experts. Data pertaining to the feasibility of the teaching materials were acquired through testing conducted on eighth-grade students in a junior high school. The present study examines the validation outcomes of teaching materials, which were categorised as highly valid. Based on the findings of the readability assessment, it was determined that the average score for the